Anaplasma phagocytophilum in Horses - Evaluation of Proinflammatory Biomarkers - Mis, Leyla; Oğuz, Bekir (Acta Scientiae Veterinariae, 2022)
ABSTRACT Background: Anaplasma phagocytophilum is an obligate intracellular pathogen transmitted by the ticks that cause equine granulocytic anaplasmosis (EGA). This pathogen is infects predominantly blood cells, principally granulocytes and especially neutrophils. A. phagocytophilum causes an acute febrile disease in horses accompanying with lethargy, loss of appetite, lameness and hemorrhages. In horses, this disease should be considered in all acute symptoms accompanied by thrombocytopenia and leukopenia identified by hematological test performed. Tick-borne pathogens have become increasingly threatening for both animals and also public health since ticks mostly carry numerous well-documented and undocumented pathogens, and the geographical range of ticks has expanded in the recent years. This research has aimed to evaluate the impact of A. phagocytophilum infection on some oxidative/nitrosative stress parameters, antioxidant enzyme activities, proinflammatory biomarkers and trace element levels in horses. Materials, Methods & Results: The present study has been carried out using blood samples collected from 93 horses aged 1-year and older. The blood samples were centrifuged and sera were separated. Serum samples stored in the freezer (-20°C) until the day of analysis. The DNA was extracted from blood and analysed by nested-PCR technique targeting 16S rRNA gene of A. phagocytophilum and then positive PCR products were sequenced. A. phagocytophilum was 6 horses (6.4%) showed positive nested-PCR results. An infected group comprised of 6 positive horses according to PCR analysis results also 6 healthy horses as control were selected. Serum SOD (Horse Superoxide Dismutase(Cu-Zn)) ELISA Kit, MPO (ELISA Assay Kit Horse Myeloperoxidase) and GPx (Horse glutathione peroxidase 1 ELISA Kit Assay), IL1 (Horse Interleukin 1 Beta ELISA Kit), IL6 (Horse Interleukin 6 ELISA Kit), TNF α (Horse Tumor Necrosis Factor Alpha ELISA Kit) and IL18 (Horse Interleukin 18 (IL18) ELISA Kit) levels were determined by ELISA reader. Serum TAS ,TOS Glucose-6-phosphate dehydrogenase (G6PD) levels were determined using colorimetric kit method. The determination of peroxynitrite was performed using spectrophotometry as described by Vanuffelen. The levels of Fe, Zn, Se, Cu, Mn, Ar, Cr, Co, Cd Ni and Pb elements were analyzed by ICP-OES. Total oxidant status (TOS) and peroxynitrite levels of the positive group infected with A. phagocytophilum were found to be higher compared with the control group (P < 0.05, respectively). Whereas, total antioxidant status (TAS), glutathione peroxidase (GPx) ,superoxide dismutase (SOD), G6PD and myeloperoxidase (MPO) levels were detected to be statistically significantly higher than the control group (P < 0.05, respectively). Cu, Mn, Se and Zn levels were also found to be lower in the infected group (P < 0.05, respectively). IL1, IL6, TNFα and IL18 from proinflammatory markers were elevated in the A. phagocytophilum infected group (P < 0.05, respectively). Discussion: The evaluation of the proinflammatory biomarkers with respect to host-parasite interactions has been suggested as a beneficial clinical tool for determination of the infection severity and diagnosis of the disease. As a conclusion, increased oxidative stress and high levels of some proinflammatory biomarkers assessed by the multibiomarker analysis carried out for the infection in the horses caused by Anaplasma phagocytophilum will provide a contribution to diagnosis, treatment and clarification of the pathogenesis. Keywords: anaplasmosis, EGA, tick-borne pathogens, pro-inflammatory cytokine, antioksidant, oxidative/nitrosative stress, equine.